Consumer society critical issues and environmental consequences - Smart, Barry (Sage, 2010)
"Has consumer culture got out of hand? Are the costs of universal access and pollution too great to bear?This comprehensive, lively and informative book will quickly be recognized as a benchmark in the field. It brings together a huge set of resources for thinking about consumer culture and examining its origins and consequences within a global context. Adept in handling a complex range of theories, Consumer Society scrupulously uses examples throughout to inform and enhance understanding. Smart writes with verve and feeling and has produced a book that simultaneously covers and enlarges our understanding of consumer culture. Clear, engaging and original, this book will be important reading for all those interested in our global culture of consumption including students of sociology, social geography and cultural studies."-Provided by publisher.